2001
DOI: 10.1097/00007632-200110010-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Vertebral Endplate Shape and Lumbar Disc Herniations

Abstract: The shape of the vertebral body margin at the endplate is an important factor contributing to the development of disc herniations at L4-L5 and L5-S1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…They can be identified with the use of medical imaging technology [ 19 , 20 ] or on dry bone [ 21 - 23 ]. Harrington et al [ 24 ] obtained similar results to Pfirrmann and Resnick [ 23 ]. They found that the size and shape of the vertebral body was associated with lower lumbar intervertebral disc herniation in a large sample of clinical patients.…”
Section: Introductionsupporting
confidence: 58%
“…They can be identified with the use of medical imaging technology [ 19 , 20 ] or on dry bone [ 21 - 23 ]. Harrington et al [ 24 ] obtained similar results to Pfirrmann and Resnick [ 23 ]. They found that the size and shape of the vertebral body was associated with lower lumbar intervertebral disc herniation in a large sample of clinical patients.…”
Section: Introductionsupporting
confidence: 58%
“…Pfirrmann and Resnick [14] found in a cadaveric study that Schmorl’s nodes were associated with a straight vertebral endplates compared to more concave ones. In addition, Harrington et al [40] have reported that the size and shape of the vertebral body related with lumbar intervertebral disc herniation. A recent skeletal study [41] showed a correlation between the morphology and size of vertebrae and the presence of Schmorl’s nodes.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that individuals with DLSS also manifested larger vertebral body dimensions [37]. Harrington et al [40] suggested that the diameters of the vertebral disc influence its ability to withstand tension during compression. Their argument rests on LaPlace’s law [42] which states that the ability of a fluid-filled tube wall to withstand tension decreases with increasing radius.…”
Section: Discussionmentioning
confidence: 99%
“…This association indicates a possible connection between the exerted axial load on the spinal vertebra and disproportion of the end plates in the development of disc pathologies such as herniation and degeneration [23]. In patients who undergo arthroplasty, undersized devices may subject the central portion of the vertebral body to higher stresses and therefore increase the risk for implant failure [24].…”
Section: Discussionmentioning
confidence: 99%